Political economy and policy analysis - Merlo, Antonio (Economist) (Abingdon, Oxon Routledge, 2019)
Most of economics takes politics for granted. Through some (often implausible) assumptions, it seeks to explain away political structures by characterizing them as stable and predictable or as inconsequential in understanding what goes on in an economy. Such attempts are misguided, and this book shows how governments and political institutions are composed of people who respond to incentives and whose behavior and choices can be studied through the lens of economics.

This book aims to bridge the gap between economics and politics, and in doing so hopes to instill in the reader a deeper appreciation for social scientific thinking. Opening with a refresher on microeconomics and an introduction to the toolkit of political economy, it ensures that the necessary building blocks are in place before building up from the level of the individual and the firm to show how a political–economic equilibrium can be achieved. The text explores how to separate primitives—the external parts of a model that we cannot affect—from outcomes—the internal parts of a model that we can. Moreover, it demonstrates that economic and political issues alike can be studied within the same general framework of analysis.

Political Economy and Policy Analysis offers readers the chance to gain a more sophisticated understanding of political processes, economic processes, and the interplay among them. Adopting an applied microeconomics approach, it will be ideal for upper-level undergraduate or postgraduate courses on political economy, public choice, or policy analysis.-- Back cover.
Includes bibliographical references and index.
Keywords: Economic policy; Policy sciences; Economics -- Political aspects